System organisation of French coordination items - Auseichyk, Yulia V. (Journal of the Belarusian State University. Philology, 2022)
The article presents the system-structural organisation of the French nuclear and peripheral items of coordination in diachrony. It is shown that the whole of explicit means of coordination is an open dynamic non-equilibrium system consisting of particular co-evolving systems representing four types of relationships: conjunctive, disjunctive, adversative, causal. It is revealed that the system of nuclear coordinators, initially united on the basis of a common functional property to establish a connection between independent predicative units, is an ordered and balanced whole of elements with two centers of attraction: proper coordination and improper coordination. It has been established that each particular system is formed gradually and is built according to the prototypical principle of «core – periphery», the uneven appearance of peripheral units leads to multidirectional trends in the design of the coordination during the French language history. The general dynamics of the use of nuclear coordinators, peripheral coordinators and their combinations is determined.
Keywords: coordinators; nuclear and peripheral items; system; system formation; use; diachrony; French language